Diffuse Dermal Angiomatosis Manifestation of Underlying Severe Peripheral Vascular Disease - Abu Baker Sheikh; Nismat Javed; Karl Stoltze (European Journal of Case Reports in Internal Medicine, 2020)
Diffuse dermal angiomatosis is a benign vascular disorder suspected in patients with cardiovascular risk factors. We report the case of a 62-year-old woman with a non-healing hip wound but no significant cardiovascular risk factors, who was found to have diffuse dermal angiomatosis on biopsy leading to the diagnosis of severe peripheral vascular disease. Her wound healed after revascularization.